SWI/SNF‐Mediated Lineage Determination in Mesenchymal Stem Cells Confers Resistance to Osteoporosis. (10th August 2015) - Nguyen, Kevin Hong; Xu, Fuhua; Flowers, Stephen; Williams, Edek A.J.; Fritton, J. Christopher; Moran, Elizabeth
Abstract: Redirecting the adipogenic potential of bone marrow‐derived mesenchymal stem cells to other lineages, particularly osteoblasts, is a key goal in regenerative medicine. Controlling lineage selection through chromatin remodeling complexes such as SWI/SNF, which act coordinately to establish new patterns of gene expression, would be a desirable intervention point, but the requirement for the complex in essentially every lineage pathway has generally precluded selectivity. However, a novel approach now appears possible by targeting the subset of SWI/SNF powered by the alternative ATPase, mammalian brahma (BRM). BRM is not required for development, which has hindered understanding of its contributions, but knockdown genetics here, designed to explore the hypothesis that BRM‐SWI/SNF has different regulatory roles in different mesenchymal stem cell lineages, shows that depleting BRM from mesenchymal stem cells has a dramatic effect on the balance of lineage selection between osteoblasts and adipocytes. BRM depletion enhances the proportion of cells expressing markers of osteoblast precursors at the expense of cells able to differentiate along the adipocyte lineage. This effect is evident in primary bone marrow stromal cells as well as in established cell culture models. The altered precursor balance has major physiological significance, which becomes apparent as protection against age‐related osteoporosis and as reduced bone marrow adiposity in adult BRM‐null mice. Stem Cells 2015;33:3028–3038 Abstract : Deficiency of BRM‐SWI/SNF favors osteoblast lineage selection and confers resistance to osteoporosis. The SWI/SNF chromatin‐remodeling complex contains either brahma‐related gene‐1 (BRG1) or brahma (BRM) as the catalytic ATPase, and functions as a master regulator of gene expression. BRG1 is required for tissuespecific gene expression throughout development, but comparatively little is known about the alternative ATPase, BRM, because BRM‐null mice develop normally. The present study now indicates that BRMSWI/SNF plays a key role in lineage selection at the osteoblast vs adipocyte decision point. Rather than favoring tissue‐specific gene expression generally, BRM‐SWI/SNF represses osteogenic gene expression and promotes adipogenic gene expression. The bone marrow stromal cell (BMSC) population in BRM‐null mice contains an increased percentage of osteoblast precursors, at the expense of cells able to differentiate along the adipocyte lineage. This is significant in conditions of osteoblast insufficiency, such that BRM‐null mice are resistant to age‐related osteoporosis.